Effectiveness of early retirement disincentives: Individual welfare, distributional and fiscal implications - Timm Bönke; Daniel Kemptner; Holger Lüthen (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2016)
In aging societies, information on how to reform pension systems is essential to policy makers. This study scrutinizes effects of early retirement disincentives on retirement behavior, individual welfare, pensions and public budget. We employ administrative pension data and a detailed model of the German tax and social security system to estimate a structural dynamic retirement model. We find that labor market participation and retirement behavior in general are strongly influenced by the level of disincentives. Further, disincentives come at the cost of increasing inequality and individual welfare losses. Still, net public returns are more than five times as high as monetarized individual welfare losses. Our estimates also suggest that similar levels of net public returns achieved by indiscriminating pension cuts are associated with individual welfare losses that are at least twice as high.
Keywords: C61; H55; J26; 330; dynamic discrete choice; retirement; tax and pension system; pension reform